Depression and its association with adverse childhood experiences in people with substance use disorders and comorbid medical illness recruited during medical hospitalization. (November 2020) - Philogene-Khalid, Helene L.; Cunningham, Eric; Yu, Daohai; Chambers, Jaclyn E.; Brooks, Adam; Lu, Xiaoning; Morrison, Mary F.
Highlights: Nearly half of medical inpatients with SUD had moderate to severe MDD. Many participants with MDD at baseline continued to have MDD 3months post discharge. Sixty-three percent (50/79) of the participants reported 4+ ACEs at baseline. Abstract: Aims: People who have experienced adverse childhood experiences (ACEs) are more susceptible to substance use disorder (SUD) and depression. The present study examined depression prevalence in hospitalized patients with SUD and examined the association of individual ACEs with major depression. Depression rates 3 months after discharge were also examined. Methods: Medical inpatients with SUD were recruited from Temple University Hospital. Depression was assessed using the Patient Health Questionnaire-9 (PHQ-9) at baseline and 3 months post-discharge. Participants were also assessed using an ACE scale at baseline. Results: Of 79 baseline participants, 48% (38) had moderate to severe major depressive disorder (MDD) with PHQ-9 scores ≥15. Among those with baseline MDD, 38% (9/24) continued to have MDD 3 months post discharge, and 42.9% (12/28) of those without MDD at baseline met criteria at 3 months. Sixty-three percent (50/79) of the participants reported 4+ ACEs at baseline. Two ACEs, Household Incarceration and Household Mental Illness, were significantly associated with having MDD at baseline and 3 months (adjusted mean PHQ-9 total score increase (SE) and p-value: 2.97 (1.35), p < .05; 5.32 (1.37), p < .005, respectively). Conclusions: In this exploratory study, nearly half of medical inpatients with substance use disorder had moderate to severe major depression, with a similar percentage of participants having MDD as outpatients at 3 months. Approximately two thirds of participants reported four or more adverse childhood experiences at baseline. Inpatient medical hospitalization should be utilized as an opportunity to engage people with SUD in multidisciplinary treatment including psychiatric, trauma informed care, and substance abuse treatment.